A weighted blanket increases pre‐sleep salivary concentrations of melatonin in young, healthy adults. (3rd October 2022) - Meth, Elisa M. S.; Brandão, Luiz Eduardo Mateus; van Egmond, Lieve T.; Xue, Pei; Grip, Anastasia; Wu, Jiafei; Adan, Ayaat; Andersson, Filip; Pacheco, André P.; Uvnäs‐Moberg, Kerstin; Cedernaes, Jonathan; Benedict, Christian
Summary: Weighted blankets have emerged as a potential non‐pharmacological intervention to ease conditions such as insomnia and anxiety. Despite a lack of experimental evidence, these alleged effects are frequently attributed to a reduced activity of the endogenous stress systems and an increased release of hormones such as oxytocin and melatonin. Thus, the aim of the present in‐laboratory crossover study (26 young and healthy participants, including 15 men and 11 women) was to investigate if using a weighted blanket (~12% of body weight) at bedtime resulted in higher salivary concentrations of melatonin and oxytocin compared with a light blanket (~2.4% of body weight). We also examined possible differences in salivary concentrations of the stress hormone cortisol, salivary alpha‐amylase activity (as an indicative metric of sympathetic nervous system activity), subjective sleepiness, and sleep duration. When using a weighted blanket, the 1 hour increase of salivary melatonin from baseline (i.e., 22:00) to lights off (i.e., 23:00) was about 32% higher ( p  = 0.011). No other significant differences were found between the blanket conditions, including subjective sleepiness and total sleep duration. Our study is the first to suggest that using a weighted blanket may result in a more significant release of melatonin at bedtime. Future studies should investigate whether the stimulatory effect on melatonin secretion is observed on a nightly basis when frequently using a weighted blanket over weeks to months. It remains to be determined whether the observed increase in melatonin may be therapeutically relevant for the previously described effects of the weighted blanket on insomnia and anxiety.